Antecedent Interest Investment Students Surakarta In The Sharia Capital Market - Muhammad Jalari; Agus Marimin (International Journal of Seocology, 2020)
The research objective was to analyze the antecedents of the investment interest of Surakarta students in the Islamic Capital Market . This type of research is a quantitative study, using a questionnaire as a research instrument. The sampling technique used was purposive sampling and accidental sampling . This research was conducted on the entire students of Surakarta who were studying f akultas / department ekonomi Islam, amounting to 2,659 people. Samples were taken of 96 respondents using the Slovin formula. Method Collecting data conductedquestionnaire . Metode analisis data is regresi linear berganda , u ji t (t-test) , ji F (F test) , koefisien determinasi with SPSS 24.00. The results of the research are the antecedents of perception, religiosity, investment benefits, minimal investment capital, motivation, return and education have a positive and significant effect both partially and simultaneously on the investment interest of Surakarta students in the Islamic Capital Market.